Structure based Study of Viral Replication - R Holland Cheng [ editor ] (World Scientific, 2008)
Addresses various themes in characterizing the cellular membrane platforms and intracellular networking, as well as the architectural aspects of cell compartments mediated by the entry and replication cycles of viruses. This book includes case studies presented with structured illuminations, including microscopy and spectroscopy.